PENGARUH UKURAN PERUSAHAAN DAN KOMPLEKSITAS PERUSAHAAN TERHADAP FEE AUDIT PADA PERUSAHAAN SEKTOR KONSUMEN PRIMER - Lisna Irmawati; Paniran; Susana Dewi (The Asia Pacific Journal Of Management Studies, 2024)
Fee Audit can cause things that are the occurrence of audit fee rate wars between fellow public accounting firms which can damage the independence of external auditors as capable and professional in their fields. Fee Audit aims to determine the factors that influence the determination of Audit Fees and the rates set by the company. This study aims to test and analyze the effect of company size, company complexity on audit fees in primary consumer sector companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021. The method used in this research is to use quantitative methods. The population in this study used 20 primary consumer sector companies listed on the Indonesia Stock Exchange in 2017-2021. And using purposive sampling technique. The analysis technique used is multiple linear regression analysis techniques using the SPSS V.25 program. The results showed that for the t test there was an influence between company complexity on Audit Fees partially, while the Company Size variable partially had no effect on Audit Fees. As for the F test, there is a significant effect between company size, company complexity, and audit fees simultaneously.